Efek Korona pada Saluran Transmisi Gardu Induk Tello Sulawesi Selatan - Rudolfus Masarrang; Lily S. Patras; Hans Tumaliang (Universitas Sam Ratulangi, 2019)
Abstrack— Transmission construction consists of Air Channels and Cable Channels. In the air channel transmission system can not be separated from interference. Both external interference and internal interference. Corona is a sphere of light around a conductor due to the occurrence of a discharge that begins on a channel surface if the strong electric field value on the channel's surface exceeds the strong value of the surrounding air field. Corona can cause corona power losses which are directly proportional to the length of a transmission line. In bright conditions, the Transmission Line will experience a loss. Keywords—Corona; Electric Field; Losses Corona; Transmission. Abstrak— Kontruksi transmisi terdiri dari dua yaitu Saluran Udara dan Saluran Kabel. Pada Sistem transmisi saluran udara tak lepas dari gangguan. Baik gangguan eksternal maupun gangguan internal. Korona adalah perpendaran cahaya diseputaran konduktor akibat terjadinya suatu pelepasan muatan yang bermula pada suatu permukaan saluran bila nilai kuat medan listrik pada permukaan saluran itu melampaui nilai kuat medan udara disekitar. Oleh sebab itu Korona dapat menimbulkan rugi – rugi daya korona yang berbanding lurus dengan panjang suatu saluran transmisi. Kata Kunci— Korona; Medan Listrik; Saluran Transmisi; Rugi – Rugi Daya Korona.